Handgrip strength and body mass index exhibit good predictive value for sarcopenia in patients on peritoneal dialysis - Li, Hongyan; Zheng, Yuanhua; Zhang, Yuanyuan; Zhang, Xiaotian; Luo, Wei; Zhu, Weiyi; Zhang, Yaqing (Frontiers in Nutrition, 2024)
AimThe diagnosis of sarcopenia in patients on peritoneal dialysis (PD) in clinics is limited owing to its relatively complicated process and the need for expensive assessment equipment. This study aimed to develop and validate sex-specific nomogram models based on body mass index (BMI), handgrip strength, and other routine follow-up examination indicators to predict sarcopenia in patients on PD.MethodsFrom March 2023 to February 2024, 699 eligible patients were recruited from the PD centers of two tertiary hospitals in southeastern China. Routine follow-up examination indicators such as age, BMI, biochemical indicators, dialysis adequacy, handgrip strength, and five-repetition sit-to-stand test, were used as potential predictive variables. Multivariate logistic regression analyses were used to separately determine the predictive factors for men and women. Nomogram models were constructed based on the results of the multivariate analyses, which were internally validated using a bootstrap re-sampling method (n = 2000). Predictive performance was validated using a receiver operating characteristic (ROC) curve.ResultsThe prevalence of sarcopenia in Chinese patients on PD was 13.92%. The nomogram models based on multivariate analyses revealed both handgrip strength and BMI as independent predictors of sarcopenia in men and women on PD. The bootstrap-corrected area under the ROC curves of the models was 0.924 (95% CI: 0.888–0.959) and 0.936 (95% CI, 0.906–0.966) for men and women, respectively. The calibration curves of both models demonstrated high consistency between the observed and anticipated values.ConclusionThe two nomogram models based on BMI and handgrip strength demonstrated good predictive ability for sarcopenia in male and female patients on PD. Subsequently, these may be used as convenient and inexpensive methods for the early detection and timely management of sarcopenia in patients on PD.